Automedicación y factores asociados durante la pandemia por COVID -19 - Maza Merchán, Lisbeth Sofía (2023)
Self-medication is the use of medicines without medical indication and without a suitable diagnosis. It is a practice that entails risks to the consumer's health and a public health problem. The present research work aimed to determine the factors associated with self-medication during the COVID-19 pandemic in nursing students of the Faculty of Human Health of the National University of Loja. The study was descriptive-correlational in scope with a non-experimental and cross-sectional design, the population consisted of 125 students who met the inclusion criteria, for data collection the survey was used as a technique and a questionnaire was used as an instrument. Data tabulation was carried out using the SPSS version 26 program. The identified results signal that 48.5% correspond to the female sex, the predominant age range was 20-22 years and 96.8% are single marital status. In relation to self-medication, 54.8% did it preventively and 92% were aware of the risks. The most used medicines were analgesics with 45.2% and 23.28% with alternative medicine, the most persistent symptom was cold or flu with 32.9%, and 96% managed to relieve the symptoms after consuming the medicines. It was established that there is a significant relationship between sociodemographic, economic, and sociocultural factors and self-medication. It is concluded that more than half of the study population self-medicate preventively and there is